Nextile PH: Terminal year end report - Ocampo, Rav Ryan A. (Animo Repository, 2022)
Venture DescriptionNextile PH was formed in 2021 by a group of De La Salle University entrepreneurship students headed by Ryan Ocampo as the CEO and Pauline Cortes, Jolleena Ramon Jao, Justin Ty, and Lon Mendoza as the department heads of each respective department. Nextile PH first launched at a physical space at HUB | Make Lab followed by taking advantage of social media platforms such as Facebook, Instagram, TikTok, and Shopee to market and sell the products. The business aims to provide its three primary products: tote bags, bucket hats, and cord organizers. The unique value proposition the business leverages on is it’s fashionable, functional, affordable, products while being responsible in sourcing materials and paying proper wages to the seamstresses for manufacturing. Nextile PH’s primary competitors are fashion staples and accessories who sell similar products and are widely known by the market. The business competes with it’s products' one-of-a-kind designs that are only available in limited quantities and the functional benefits of organization the user can receive from using it. Venture OrganizationThe management of Nextile PH consists of 5 members namely Ryan Ocampo, Pauline Cortes, Jolleena Ramon Jao, Justin Ty, and Lon Mendoza who became acquainted last school year 2020 during the pandemic when a shift to an online setup was implemented. Ever since then the group has been planning the execution and growth of this project at its earliest convenience. The team is diverse with various sets of skills and experiences that will prove to be beneficial for the duration of the business. Ryan Ocampo, as the CEO, has been immersed in internships and training which makes him qualified to be the business’ CEO. Pauline Cortes, as the production and distribution head, has personal experience in starting and managing her own business. Jolleena Ramon Jao, as the finance head, has had the position of the treasurer in her previous school. Justin Ty, as the marketing head, is knowledgeable of the market industry and creating copies. Lon Mendoza, as the external relations head, has participated in seminars about entrepreneurship and partnerships. Venture MarketNextile PH falls under the fashion industry, more specifically under the accessories category. The fashion industry in the Philippines is forecasted to reach $788 million by the end of 2021 (Statista, 2021b). In relation with the tote bags, the projected revenue for bags industry segment that are being sold in the e-commerce industry in the Philippines is expected to reach $71 million by the end of 2021 with an annual growth rate of 14.14% for the next 4 years (Statista, 2021a). Currently situated in the COVID-19 pandemic, Nextile PH primarily targets Millennials and Gen Z and Millennials the “organized and fashionable consumer” behavior as the company believes in encouraging a lifestyle that one can be stylish without breaking the bank and have convenience in bringing everyday essentials wherever and whenever they need. The management team will also be the sales representatives of the business where quota selling will be implemented. Venture Operations Through online platforms such as Facebook, Instagram, and Shopee as well as the partner physical retailer HUB Make Lab, the business will be maximizing its customer reach and sales. Three bank channels namely GCash, BDO, and Metrobank will be used to receive payments from customers. Delivery options shall also be through same-day delivery or parcel delivery with an additional option to have cash on delivery for the customer’s convenience. Each member of the business will be working remotely and utilize Google Suite and other online tools to communicate and collaborate with. Monthly meetings will also be held to align the team and goals. Venture Financing Nextile PH is a business that would require Php30,000 to kick start its operations and the duration of operations and partnership will occur for 1 year. Each partner will have 20% of the ownership in accordance with each person’s capital contribution. The capital will be used in purchasing supplies, production labor, and marketing. The business is projected to be able to accumulate a total sales of ₱102,372 and gross profit of ₱58,983.33 which will be achieved when over 394 products are sold. Based on the profitability ratios, the company is able to achieve a ROA of 58.25%, ROE of 76.25%, and a ROI of 139.54% which would be up for consideration in terms of moving forward with the business.